IBM System Storage DS8000 performance monitoring and tuning - Westphal, Axel (IBM Corporation, International Technical Support Organization, 2016)
This IBM® Redbooks® publication provides guidance about how to configure, monitor, and manage your IBM DS8880 storage systems to achieve optimum performance, and it also covers the IBM DS8870 storage system. It describes the DS8880 performance features and characteristics, including hardware-related performance features, synergy items for certain operating systems, and other functions, such as IBM Easy Tier® and the DS8000® I/O Priority Manager. The book also describes specific performance considerations that apply to particular host environments, including database applications. This book also outlines the various tools that are available for monitoring and measuring I/O performance for different server environments, and it describes how to monitor the performance of the entire DS8000 storage system. This book is intended for individuals who want to maximize the performance of their DS8880 and DS8870 storage systems and investigate the planning and monitoring tools that are available. The IBM DS8880 storage system features, as described in this book, are available for the DS8880 model family with R8.0 release bundles (Licensed Machine Code (LMC) level 7.8.0).
"This edition applies to Version 8.0 of the IBM DS8884 and DS8886 models (product numbers 2831--2834) and Version 7.5 of the IBM DS8870 (product numbers 2421--2424)"--Cover verso. - Number on back cover: SG24-8318-00. - Includes bibliographical references. - Description based on online resource; title from cover (Safari, viewed April 21, 2016)
Keywords: Storage area networks (Computer networks); Computer architecture; Computer systems; IBM computers -- Programming; Computer Systems; Réseaux de stockage (Informatique); Ordinateurs; Architecture; Systèmes informatiques; IBM (Ordinateurs); Programmation; IBM computers; Programming